Construction of a mathematical model of lamb wave propagation in a steel pipeline with a protective outer coating - S. O. Gaponenko; A. E. Kondratiev; G. R. Mustafina (Известия высших учебных заведений: Проблемы энергетики, 2022)
THE PURPOSE. Adapt the method of measuring the propagation of Lamb waves in thin two-layer plates to the study of the dependence of the phase velocity on the technical condition of pipelines with a protective outer coating. To perform a modification of the numerical-analytical algorithm for measuring the thickness of the coating and areas of non-adhesion of materials in thin two-layer plates for vibroacoustic diagnostics of technical pipelines. To investigate the propagation of a symmetric Lamb wave in a steel pipeline with a protective outer coating. METHODS. To solve the problem of localizing damage to technical pipelines, traditional methods of non-destructive testing based on vibroacoustic diagnostics are considered. RESULTS. Work on the construction of a mathematical model of the dependence of the propagation of the phase velocity of the Lamb wave on the thickness of the object under study has been carried out. The numerical analysis of the measurements was carried out using the example of thin two-layer segments of pipelines. The presence of changes in the thickness of the pipeline is taken as the effect of material defects on the propagation parameters of the Lamb wave mode. CONCLUSION. A numerical-analytical method for calculating the propagation of a symmetric Lamb wave mode in a thin segment is presented. The dependence of the propagation velocity of Lamb waves on the segment thickness is demonstrated. Based on the described technique, it seems possible to estimate not only the thickness of the segment and the area of non-adhesion of the layers, but also the total area of the defective area. This will allow in the future to record the relative changes in the thickness of the walls of pipelines to determine changes in the physical properties of the material or the presence of a defect.